(untitled) - Phillips, Keith (Malaysia, 2004)
From this small volume you will learn - straight from the Scriptures - how to: Excel in your relationships with others, build character, overcome personal weaknesses and bad habits, have more love, give more love, have a closer relationship with God, receive God's spiritual and material blessings, be happy, live life to the full. Over 50 topics in all. Bible keys to happier living's thorough content and easy-to-follow format also make it a favorite with parents, teachers, and mentors
Keywords: Bible -- Indexes